2016
DOI: 10.1177/0748233715602833
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between urinary cadmium and thyroid hormones in outdoor workers exposed to urban stressors

Abstract: Our early results seem to point out that occupational exposure to low concentrations of Cd present in urban air affects the thyroid hormone levels in exposed workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…These gender-based differences are difficult to explain and may be the consequence of toxicokinetics and hormonal differences between sexes that certainly influence observed responses. Studies by Rosati et al [ 32 ] and Jurdziak et al [ 33 ] have added the factor of occupational exposure to Cd. An outdoor study on 277 individuals of both sexes exposed to urban pollutants has found a negative correlation between urinary Cd levels and free T3 and T4 levels and a positive correlation between Cd urinary levels and TSH levels, showing that occupational exposure to the low Cd concentration present in urban air affects thyroid function [ 32 ].…”
Section: Cadmium Effects On Thyroid Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These gender-based differences are difficult to explain and may be the consequence of toxicokinetics and hormonal differences between sexes that certainly influence observed responses. Studies by Rosati et al [ 32 ] and Jurdziak et al [ 33 ] have added the factor of occupational exposure to Cd. An outdoor study on 277 individuals of both sexes exposed to urban pollutants has found a negative correlation between urinary Cd levels and free T3 and T4 levels and a positive correlation between Cd urinary levels and TSH levels, showing that occupational exposure to the low Cd concentration present in urban air affects thyroid function [ 32 ].…”
Section: Cadmium Effects On Thyroid Functionmentioning
confidence: 99%
“…Studies by Rosati et al [ 32 ] and Jurdziak et al [ 33 ] have added the factor of occupational exposure to Cd. An outdoor study on 277 individuals of both sexes exposed to urban pollutants has found a negative correlation between urinary Cd levels and free T3 and T4 levels and a positive correlation between Cd urinary levels and TSH levels, showing that occupational exposure to the low Cd concentration present in urban air affects thyroid function [ 32 ]. Another study on workers occupationally exposed to Pb, Cd, and arsenic also confirmed that higher blood Cd concentrations amplify the risk of abnormal hormonal thyroid function evaluated by elevated TSH levels [ 33 ].…”
Section: Cadmium Effects On Thyroid Functionmentioning
confidence: 99%
“…For average UCd level, the odds of female were lower than that of males (Table 2); the reason might come from the sample sizes. Moreover, it has been found that endogenous hormones contribute to the UCd burden [43,44]. The participants in our survey were all native residents, and most had been living in the study site more than 25 years.…”
Section: Discussionmentioning
confidence: 99%
“…For average UCd level, the odds of female were lower than that of males (Table 2); the reason might come from the sample sizes. Moreover, it has been found that endogenous hormones contribute to the UCd burden [40,41].…”
Section: Discussionmentioning
confidence: 99%